Aspirin-loaded nanoexosomes as cancer therapeutics - Tran, Phuong H.L.; Wang, Tao; Yin, Wang; Tran, Thao T.D.; Nguyen, Tuong N.G.; Lee, Beom Jin; Duan, Wei (International Journal of Pharmaceutics, 2019)
The long history of discovery and recently encouraging studies of the anti-cancer effect of aspirin promise a closer step to widely used aspirin-based medication in cancer therapy. To resolve the poor water-solubility of aspirin and low encapsulation efficiency of exosomes for further developing a new delivery of aspirin as anti-cancer treatment, our nanoamorphous exosomal delivery platform was established. In this study, the anti-tumour effects of nanoamorphous aspirin-loaded exosomes with exosomes derived from breast and colorectal cancer cells, were comprehensively studied using both in vitro and in vivo models. These exosomes displayed enhanced cellular uptake via both clathrin-dependent and -independent endocytosis pathways, and significantly improved cytotoxicity of aspirin to breast and colorectal cancer cells, accompanied by the enhanced apoptosis and autophagy. Remarkably, this nanoamorphous exosomal platform endowed aspirin with the unprecedented cancer stem cell eradication capacity. Further animal study demonstrated that this developed exosomal system was able to efficiently deliver aspirin to in vivo tumours. The active targeting of these exosomes to tumour was further improved by conjugating an aptamer specifically targeting EpCAM protein. Hence, this nanoamorphous structured exosome system effectively transformed aspirin into a potential cancer stem cell killer with distinguished properties for clinical translation.
Keywords: Animals; Antineoplastic Agents; Apoptosis; Aspirin; Autophagy; Breast Neoplasms; Colorectal Neoplasms; Drug Carriers; Drug Delivery Systems; Endocytosis; Exosomes; Female; HT29 Cells; Humans; Mice, Inbred NOD; Mice, SCID; Nanoparticles; Neoplastic Stem Cells; Tissue Distribution; Xenograft Model Antitumor Assays; Aspirin; Breast cancer; Cancer stem cell; Colorectal cancer; Exosome